Do you know what I'm thinking about? Examining children's mental states understanding in conversations with peers. - Ho, SiRong. (2010)
The present study investigates theory of mind (ToM) development in bilingual children. Fifteen 3-year-old and seventeen 5-year-old Singaporean bilingual children were recruited from a local childcare centre. Participants’ conversations with peers were observed and transcribed for references to mental states. Specifically, the hypotheses were (a) the use of mental-states utterances, and (b) reference to mental states of self and others would increase from 3 to 5 years old. Results revealed that 5-year-olds use mental-states utterances more frequently than 3-yearolds. There was also an increase in reference to children’s own mental states from 3 to 5 years old, suggesting a deeper mental-states understanding. Findings were discussed in relation to children’s ToM development as a universal phenomenon.